Practices of PPA and PPR on public procurement in Bangladesh Water Development Board: A Critical Review - Hasan, Mahbube Moula Md. Mehedy (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2012.